The role of self-efficacy as a mediating variable in CareerEDGE employability model: the context of undergraduate employability in the North-East Region of Nigeria - Wujema, Baba Kachalla; Mohd Rasdi, Roziah; Zaremohzzabieh, Zeinab; Ahrari, Seyedali (Multidisciplinary Digital Publishing Institute, 2022)
Background: Tertiary institutions are facing increasing pressure to produce employable undergraduates who can drive the sustainability of strong economic growth and development. As such, responsibility lies with the higher education sector in ensuring undergraduates’ readiness for entry to the labor market, thus joining the ranks of those already employable. Thus, this study applied the CareerEDGE model as a theoretical basis to investigate the factors associated with undergraduate employability. The mediating effect of self-efficacy on the predictive relationships was also examined. (2) Methods: Data were collected from a sample of 264 from six universities in the North-East region of Nigeria. Partial least squares structural equation modeling was used to perform the data analysis in this study. (3) Results: Results revealed that the five constructs of the CareerEDGE model (career development learning; work experience; degree subject knowledge, skills, and understanding; generic skills; and emotional intelligence) are positively associated with undergraduate employability. Self-efficacy was found to mediate this relationship. Altogether, these results signal that the CareerEDGE model contributes to undergraduate employability and that self-efficacy is instrumental in elucidating this relationship. The results add to the extant knowledge on the impact of the CareerEDGE constructs on students’ approaches to careers. (4) Conclusions: The findings have significant implications for higher education institutions and career practitioners in identifying ways of enhancing undergraduates’ career planning strategies within a more challenging labor market context.